Use of Echocardiography in The Intensive Care Unit - Burak Eşkin; Ahmet Coşar (Galenos Yayinevi, 2012)
Echocardiography is a diagnosis and research method that allows us to learn about anatomical and mechanical functions of the heart by using ultrasonic sound waves. Echocardiography is rapid and non-invasive way to image the cardiac structures in intensive care unit. Preload, myocardial and ventricular functions, valve diseases and vegetations, cardiac tamponade, pulmonary embolism, aortic dissection, and cardiac arrest can be investigated with echocardiography in intensive care unite. Indications for echocardiography, views of the main pathologies encountered in intensive care unite, commonly used windows in echocardiography are included in this article. (Journal of the Turkish Society Intensive Care 2012; 10: 28-36)